Cross-country ski vibrations and possible mechanisms of their influence on the free gliding - Koptyug, A.; Bäckström, M.; Trinnsten, M.; Carlsson, P. (Procedia Engineering, 2012)
Present paper describes the results of experimental studies on the self-induced and forced vibrations of loaded cross country skis and presents the discussion on the possible mechanisms causing such vibrations and the ways they can influence the friction between the ski running surface and the snow. Studied vibrations of gliding skis are most probably caused by the frictional effects. Mechanisms involved are similar to the ones causing the brake disc squeal or the violin string excitation by the bow. Major factors responsible for the development of these vibrations such as micro roughness of the surfaces, nonlinearities in the material properties, thermo-elastic instabilities and instabilities due to decreasing friction with increasing sliding velocity are also common for the case of gliding skis. The results of this study indicate that the ski vibration pattern both in amplitude and in frequency could influence the ski gliding properties. Though it seems quite feasible that the control of the cross country ski vibrations can improve the gliding performance, further systematic studies are needed to confirm it and to formulate the consecutive strategies of cross country ski design improvement.